Perceptions about the Health Effects of Passive Smoking among Bangladeshi Young Adults - Sultana, Rabeya; Akter, Jesmin; Nahar, Nasreen; Faruque, Mithila; Ara, Begum Rowshan; Ahmed, Md. Kapil (International Journal of Statistics in Medical Research, 2016)
Passive smoking is now firmly established as a significant cause of morbidity and mortality. Assessment of young adults’ perceptions, understanding and knowledge of the health effects of passive smoking may promote educational endeavours to increase awareness of the passive smoking-linked health effects and to facilitate interventions. The study, therefore, assessed the perceptions of young adults in Bangladesh about the health effects of passive smoking. This cross-sectional descriptive study was conducted among 656 young adults in two districts under Dhaka division of Bangladesh. The study used a multistage cluster random sampling approach. Binary logistic regression was used for identifying the predictors of perceptions that passive smoking is harmful. The vast majority of the respondents believed that passive smoking causes illnesses but the knowledge of specific health effects was limited. Most (87.2%) respondents perceived that passive smoking causes ‘some’ or ‘a lot’ of harm to health of both adults and children. However, disparities in perceptions were prevalent across their educational levels. The results of logistic regression analysis showed that, after adjusting other factors, respondents who had nine or more years of education were 6.7 times likelihood of perceiving that passive smoking causes “some” or “lot of harm” compared to those who had no education. The findings suggested that more efforts, including some appropriate measures to address knowledge gaps, are needed to increase better perception about the harmful effects of passive smoking among young adults.